2000
DOI: 10.1111/j.1151-2916.2000.tb01584.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of (Na2O–MgO)–CaO–Al2O3–SiO2 Glassy Systems Formulated from Waste Products

Abstract: Aluminosilicate and silicate glass-ceramics were obtained from controlled devitrification of CaO-Al 2 O 3 -SiO 2 glassy systems starting from Spanish and Italian coal fly ash or Italian municipal incinerator slag mixed with other byproducts, such as glass cullet and dolomite. The nucleation mechanism and the crystallization kinetics were investigated by thermal, diffractometric, and microstructural measurements. Moreover, the experimentally observed devitrification and the identification of the crystalline pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 8 publications
1
38
0
3
Order By: Relevance
“…This . The most frequent crystallisation mechanism, the one at the surface, has proved to be quite an effective method for enhancing the strength of glass (Barbieri et al, 2000b). It is concluded that plasma treatment of APC residues produces a highly inert and stable glass which is suitable for disposal in inert landfill or use in bulk civil engineering applications.…”
Section: Discussionmentioning
confidence: 99%
“…This . The most frequent crystallisation mechanism, the one at the surface, has proved to be quite an effective method for enhancing the strength of glass (Barbieri et al, 2000b). It is concluded that plasma treatment of APC residues produces a highly inert and stable glass which is suitable for disposal in inert landfill or use in bulk civil engineering applications.…”
Section: Discussionmentioning
confidence: 99%
“…Barbieri and co-workers have published a series of papers [103][104][105] on glass-ceramics produced from fly ash mixed with other waste materials. The other wastes were mainly float dolomite (CaMg(CO 3 ) 2 ) from mineral extraction operations, which was used to increase CaO and MgO content, and glass cullet to increase the amount of SiO 2 , Na 2 O and CaO present in the parent glass.…”
Section: Melting and Subsequent Heat Treatmentmentioning
confidence: 99%
“…Barbieri and co-workers were able to produce a series of glass-ceramics containing different phases [103][104][105]. For example glass-ceramics from fly ash with only glass cullet as an additive had acicular wollastonite as the crystalline phase whereas, with the further addition of dolomite, this phase was only found after heat treatment in a narrow temperature range around 1000°C and most heat treatments resulted in a microstructure with dendritic pyroxene (diopside) and a small amount of acicular feldspar (anorthite).…”
Section: Melting and Subsequent Heat Treatmentmentioning
confidence: 99%
“…Therefore, this must be considered as the optimum crystallisation treatment to transform the PG glass into a glass-ceramic material. It is well known that wollastonite is a common crystalline phase in glass-ceramics formulated with high CaO content 6,16,19, and in conventional ceramic tiles manufactured by a fast-firing process. Wollastonite crystallisation gives high mechanical resistance to tile products and a high content of this phase in a sintered glass-ceramic will imply higher strength of the final products.…”
Section: Static (Quenched) Experiment Ttt Curves and Xrd Phase Identmentioning
confidence: 99%
“…In thermal plasma vitrification, the heat generated is used to treat hazardouswastes containing metals, inorganic oxides and/or organics at temperatures above 1500ºC, at which point metal containing wastes are melted and organic contaminants are thermally destroyed. The plasma vitrification yields a leach-resistant monolithic glassy slag, which is environmentally safe for landfill disposal or can be reused as glassceramic for construction materials [4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%